2005
DOI: 10.1086/431740
|View full text |Cite
|
Sign up to set email alerts
|

Secular Evolution in Mira Variable Pulsations

Abstract: Stellar evolution theory predicts that asymptotic giant branch (AGB) stars undergo a series of short thermal pulses that significantly change their luminosity and mass on timescales of hundreds to thousands of years. These pulses are confirmed observationally by the existence of the short-lived radioisotope technetium in the spectra of some of these stars, but other observational consequences of thermal pulses are subtle and may only be detected over many years of observations. Secular changes in these stars r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 54 publications
(88 reference statements)
9
85
2
Order By: Relevance
“…Among the SCh change type stars, BH Cru seems to have stopped or maybe even reversed its period increase. A deceleration of the period increase was proposed by Templeton et al (2005). RU Vul has continued its period decrease (also found by Templeton et al 2008), and the pulsation is very weak now.…”
Section: Present-day Periodsmentioning
confidence: 56%
See 2 more Smart Citations
“…Among the SCh change type stars, BH Cru seems to have stopped or maybe even reversed its period increase. A deceleration of the period increase was proposed by Templeton et al (2005). RU Vul has continued its period decrease (also found by Templeton et al 2008), and the pulsation is very weak now.…”
Section: Present-day Periodsmentioning
confidence: 56%
“…Figure 1 shows the Coralie spectrum of BH Cru, smoothed to the resolution of classification spectra to make the Notes. The meaning of the columns is as follows: (1) name listed in Simbad; (2) period change type; (3) range of spectral type; (4) heliocentric radial velocity; (5) presence of Tc, this paper; (6) presence of Tc, previous studies; (7) effective temperature; (8) abundance of Li; (9) rate of period change; (10) period as given in Templeton et al (2005); (11) period found in this study; (12) mean J − K colour; (13) absolute K magnitude; (14) bolometric magnitude. References of previous studies on Tc content: (1) Little-Marenin & Little (1979); (2) Little et al (1987); (3) Vanture et al (1991); (4) Merrill (1952); (5) Uttenthaler & Lebzelter (2010); (6) Lebzelter & Hron (1999).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an M8-9-type Mira Ceti variable found by Wolf (1904) with P = 424.75±1.77 d (Templeton et al 2005) and silicate dust emission (Sloan & Price 1998;Speck et al 2000). In particular, the 9.7 and 18 µm silicate dust feature originates from the circumstellar envelopes of oxygenrich asymptotic giant branch stars (Kwok et al 1997).…”
Section: Known Background Giants X Ori (No 29)mentioning
confidence: 92%
“…Large period changes, though rare, have been well documented in a few stars since the earliest work of Sterne & Campbell (1937), and centuries-long historical light curves for a few Miras show significant changes over time (Sterken et al 1999;Percy & Au 1999;, even if periods are relatively stable at present. Templeton et al (2005) used the American Association of Variable Star Observers (AAVSO) data archives to search for large, longterm period changes in 547 Mira variables, including o Ceti itself. Although o Ceti was not flagged as having a large period change, the significance criteria used in that paper were very high, and did not rule out period changes at the level of a few percent.…”
Section: Introductionmentioning
confidence: 99%